2016
DOI: 10.1371/journal.pone.0151865
|View full text |Cite
|
Sign up to set email alerts
|

BRAF, PIK3CA, and HER2 Oncogenic Alterations According to KRAS Mutation Status in Advanced Colorectal Cancers with Distant Metastasis

Abstract: BackgroundAnti-EGFR antibody–based treatment is an important therapeutic strategy for advanced colorectal cancer (CRC); despite this, several mutations—including KRAS, BRAF, and PIK3CA mutations, and HER2 amplification—are associated with the mechanisms underlying the development of resistance to anti-EGFR therapy. The aim of our study was to investigate the frequencies and clinical implications of these genetic alterations in advanced CRC.MethodsKRAS, BRAF, and PIK3CA mutations were determined by Cobas real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
7
35
1
1
Order By: Relevance
“…Our data suggest that right-sided tumors are less likely to be HER2 positive, in line with previous reports showing that chromosomal regions hosting receptor tyrosine kinases are more often amplified in distal than in proximal carcinomas [21,22]. On one hand, however, this should not preclude testing for HER2 based on sidedness, as some positive cases might be missed; on the other hand, the predominant presence of HER2 positivity in the left colon carries therapeutic implications by mitigating the clinical paradigm according to which left-sided CRCs as a whole are more sensitive to EGFR-targeted treatment [23].…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that right-sided tumors are less likely to be HER2 positive, in line with previous reports showing that chromosomal regions hosting receptor tyrosine kinases are more often amplified in distal than in proximal carcinomas [21,22]. On one hand, however, this should not preclude testing for HER2 based on sidedness, as some positive cases might be missed; on the other hand, the predominant presence of HER2 positivity in the left colon carries therapeutic implications by mitigating the clinical paradigm according to which left-sided CRCs as a whole are more sensitive to EGFR-targeted treatment [23].…”
Section: Discussionsupporting
confidence: 92%
“…81,83,84 Mutations in KRAS are widely accepted as predictors of resistance to anti-EGFR antibody therapies in patients with mCRC. 85 In the current study and previous reports, 34,86 ERBB2 amplification strongly correlated with a lack of RAS and BRAF alterations. In addition, although we did not observe a difference between rectal and colonic tumors in terms of frequency of ERBB2 amplifications, other studies have demonstrated a strong correlation between ERBB2 amplification and left colonic tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies showed that distal and proximal colon cancers differ in terms of molecular, pathological, and clinical features [26,27]. The present data revealed that there was not any correlation between LRIG1 expression and bilateral and peritoneal CRC metastasis (P > 0.05) and also with age, synchronous or metachronous CRC or primary tumor location (P > 0.05).…”
Section: Discussioncontrasting
confidence: 50%